Perfil de metilação dos genes de reparo de fita simples do DNA em pacientes portadores de síndrome mielodisplásica e em agricultores expostos a agrotóxicos - Costa, Marilia Braga (2022)
Myelodysplastic syndrome (MDS) is defined as a heterogeneous group of hematopoietic progenitor cell clonal diseases characterized by cytopenias and bone marrow dysplasia with a risk of progressing to acute myeloid leukemia. Its etiology is mainly related to age, but one of the risk factors is exposure to pesticides that can lead to aberrant reprogramming of the genome by DNA methylation. The present study has as main objective to evaluate the methylation profile of DNA repair genes in three study groups: a group with a risk factor for the disease, characterized by farmers; a second group composed of patients with MDS; a third group composed of healthy people and not exposed to pesticides at any time in life. In addition to methylation analyzes, this work associates methylation results with gene expression data obtained in previous studies. The methylation profile of genes related to the simple DNA strand repair mechanism (CSA, CSB, XPA, XPC and XPG) was evaluated with the pyro-sequencing technique using bone marrow samples from the three groups and we performed the karyotype analysis of bone marrow cells by G-Band to investigate cytogenetic changes. In the analysis of the methylation profile of the groups of farmers, it was observed that the group of ecological agriculture presented a higher percentage of methylation of the XPA gene compared to the exposed groups. Regarding the variables of SMD, patients under the age of 60 years showed a higher percentage of methylation for the XPA and CSB gene compared to patients aged equal or above. Patients classified in the initial forms of SMD showed a higher percentage of methylation compared to the advanced forms for the XPA gene. Furthermore, in the risk classification of the R-IPSS, low-risk patients showed a higher percentage of methylation compared to patients classified in the high-risk group. Regarding the analyzes between the groups, there was a higher percentage of methylation in the SMD group compared to exposed farmers and the control group. The SMD group was subdivided into its initial and advanced forms and methylation was evaluated in relation to exposed farmers and the control group. A higher percentage of methylation was observed in the initial forms group compared to the advanced forms group and the exposed farmers group, as well as the initial forms also showed a higher percentage of methylation compared to the control group. The correlation analyzes between expression and methylation of both farmers and patients with MDS were not correlated, suggesting that the change in the expression of these genes is not motivated by the DNA methylation mechanism.